Public sector corruption, FDI and sustainable development in Africa: Does the pollution halo or haven hypothesis hold in Ghana? - Joseph Ato Forson (Scientific African)
This paper examines the effects of corruption and FDI on sustainable development in Africa, particularly Ghana. The study observes the behaviour of firms using foreign direct investment to track MNEs' role in carbon emission. The study employs a quantitative approach with an ex-post facto research design type to inquiry using data from the World Bank, the Global Footprint Network and Transparency International from 1980 to 2023. The symmetric result discloses that corruption and FDI depress sustainability significantly in the long run. In the short run, it turns out that corruption and FDI stimulate sustainability. However, the short-run asymmetric effect shows that the positive and negative shocks of corruption and FDI exude negative effects on sustainability. This provides strong and consistent evidence of the pollution haven hypothesis of FDI in Ghana. Therefore, firms under the one-district, one-factory (1D1F) flagship policy and beyond must be encouraged to adhere to the strict carbon policy of the host country. The decision of the government to introduce an emission tax in the 2024 budget is tenable but the tax must be properly targeted to achieve the desired outcome.